The ultrastructure of the kinetochore and kinetochore fiber in Drosophila somatic cells. - Maiato, H.; Hergert, P.J.; Moutinho-Pereira, S.; Dong, Y.; Vandenbeldt, K.J.; Rieder, C.L.; McEwen, B.F. (Chromosoma, 2006)
Drosophila melanogaster is a widely used model organism for the molecular dissection of mitosis in animals. However, despite the popularity of this system, no studies have been published on the ultrastructure of Drosophila kinetochores and kinetochore fibers (K-fibers) in somatic cells. To amend this situation, we used correlative light (LM) and electron microscopy (EM) to study kinetochores in cultured Drosophila S2 cells during metaphase, and after colchicine treatment to depolymerize all microtubules (MTs). We find that the structure of attached kinetochores in S2 cells is indistinct, consisting of an amorphous inner zone associated with a more electron-dense peripheral surface layer that is approximately 40-50 nm thick. On average, each S2 kinetochore binds 11+/-2 MTs, in contrast to the 4-6 MTs per kinetochore reported for Drosophila spermatocytes. Importantly, nearly all of the kinetochore MT plus ends terminate in the peripheral surface layer, which we argue is analogous to the outer plate in vertebrate kinetochores. Our structural observations provide important data for assessing the results of RNAi studies of mitosis, as well as for the development of mathematical modelling and computer simulation studies in Drosophila and related organisms.